2014
DOI: 10.1074/jbc.m113.492140
|View full text |Cite
|
Sign up to set email alerts
|

Androgen Receptor Splice Variant AR3 Promotes Prostate Cancer via Modulating Expression of Autocrine/Paracrine Factors

Abstract: Background: AR splice variants may play a critical role in prostate cancer. Results: AR3 modulates expression of tumor-promoting growth factors and promotes epithelial-mesenchymal transition, leading to development of prostatic intraepithelial neoplasia. Conclusion: AR3 promotes prostate cancer by modulating multiple tumor-associated autocrine/paracrine factors. Significance: Our findings provide new insights into mechanisms by which AR3 contributes to prostate cancer despite its heterogeneous expression patte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
71
0
3

Year Published

2014
2014
2019
2019

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 60 publications
2
71
0
3
Order By: Relevance
“…They also found that increased mesenchymal signatures in prostate tumors from patients treated with androgen-deprivation therapy [16]. A recent study further suggest that AR3 driven PCa initiation and progression can occur in a transgenic mouse model (AR3Tg) by modulating TGF-beta pathway, which was associated with the elaboration of EMT signatures and increasing prostatic progenitor cell population [11]. These in vivo results confirmed our findings indicating that androgen deprivation-mediated increased expression of AR3 contributes to the development of CRPC and mCRPC by regulating EMT and stem cell pathways.…”
Section: Discussionmentioning
confidence: 99%
“…They also found that increased mesenchymal signatures in prostate tumors from patients treated with androgen-deprivation therapy [16]. A recent study further suggest that AR3 driven PCa initiation and progression can occur in a transgenic mouse model (AR3Tg) by modulating TGF-beta pathway, which was associated with the elaboration of EMT signatures and increasing prostatic progenitor cell population [11]. These in vivo results confirmed our findings indicating that androgen deprivation-mediated increased expression of AR3 contributes to the development of CRPC and mCRPC by regulating EMT and stem cell pathways.…”
Section: Discussionmentioning
confidence: 99%
“…AR-V expression is found to be common in tumor metastases; furthermore, levels of variant expression directly correlate with accelerated disease progression and shorter cancer-specific survival [36, 101]. Experiments on mice have shown that AR v567es can induce autonomous tumor formation and proliferation [54], and AR-V7 expression leads to the expression of tumor promoting growth factors such as TGFβ2 and IGF1 [83]. These findings suggest that AR-Vs are biologically significant and may contribute to clinical progression of prostate cancer.…”
Section: Androgen Receptor Splice Variantsmentioning
confidence: 99%
“…However, the main mechanism of dexamethasone is unclear. In our previous study, modification of hormone affected the function of pericytes in prostate glands [2]. Under chronic inflammation, cytokines such as VEGF, IL17, induced transformation of cell types and neovascularization involving pericytes in periodontitis rats [3].…”
Section: Discussionmentioning
confidence: 99%